TRANSFORMASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ERA DIGITAL - Lailatul Qomariyah; Kameliatul Ahlaq; Ansori (Makkah: Journal Of Islamic Studies, 2026)
The transformation of Islamic Religious Education (PAI) learning in the digital era is a significant phenomenon reflecting a paradigm shift in education from conventional models to technology-based learning that is more interactive, flexible, and student-centered. This study aims to analyze the dynamics of this change, including the opportunities, challenges, and implications for the PAI learning process amidst the development of global digital technology. The method used is library research with a qualitative approach through the analysis of various relevant scientific literature. The results of the study indicate that the integration of digital technology can increase the accessibility of learning resources, strengthen student engagement, and encourage independent learning. However, there are significant challenges such as low digital literacy of educators, the potential for religious disinformation, and the need to strengthen technology-based pedagogical competencies. Therefore, the transformation of PAI learning needs to be directed at a balance between the use of digital technology and the strengthening of authentic Islamic values ​​to remain relevant in shaping students' character in the global era.